A Comparative Reliability and Performance Study of Different Stent Designs in Terms of Mechanical Properties: Foreshortening, Recoil, Radial Force, and Flexibility. Issue 4 (5th March 2013) - Kim, Dong Bin; Choi, Hyuk; Joo, Sang Min; Kim, Han Ki; Shin, Jae Hee; Hwang, Min Ho; Choi, Jaesoon; Kim, Dong‐Gon; Lee, Kwang Ho; Lim, Chun Hak; Yoo, Sun Kook; Lee, Heung‐Man; et al.
Abstract This study seeks to improve the mechanical performance of stents by conducting reliability performance testing and finite element method (FEM)‐based simulations for coronary stents. Three commercially available stent designs and our own new design were tested to measure the factors affecting performance, specifically foreshortening, recoil, radial force, and flexibility. The stents used in the present experiments were 3 mm in working diameter and 18 mm of working length. The results of the experiments indicate that the foreshortening of stents A, B, C, and our new design, D, was equivalent to 2.25, 0.67, 0.46, and 0.41%, respectively. The recoil of stents A, B, C, and D was 6.00, 4.35, 3.50, and 4.36%, respectively. Parallel plate radial force measurements were A, 3.72 ± 0.28 N; B, 3.81 ± 0.32 N; C, 4.35 ± 0.18 N; and D, 4.02 ± 0.24 N. Radial forces determined by applying uniform pressure in the circumferential direction were A, 28.749 ± 0.81 N; B, 32.231 ± 1.80 N; C, 34.522 ± 3.06 N; and D, 42.183 ± 2.84 N. The maximum force of crimped stent at 2.2‐mm deflection was 1.01 ± 0.08 N, 0.82 ± 0.08 N, 0.92 ± 0.12 N, and 0.68 ± 0.07 N for each of stents A, B, C and D. The results of this study enabled us to identify several factors to enhance the performance of stents. In comparing these stents, we found that our design, stent D, which was designed by a collaborative team from seven universities, performed better than the commercial stents across all parameter of foreshortening, recoil, radial force, and flexibility.